The meta-constitution: amendment, recognition, and the continuing puzzle of supreme law in Canada. (2nd January 2016) - Hamill, Sarah E.
ABSTRACT: This paper uses the idea of the meta-constitution to interrogate issues with Canada's constitutional amendment and recognition procedures. Put simply, the meta-constitution is that part or parts of a written constitution which are self-referential. Typically, meta-constitutions explain what document(s) make up the constitution and how the constitution can be amended. Most meta-constitutions are simple but Canada's is not and the difficulties with Canada's meta-constitution highlight the key legal and political role that this often overlooked constitutional feature plays. In 2014, the Supreme Court of Canada issued decisions in two reference cases which dealt with meta-constitutional issues and, as argued in this paper, the Court used the meta-constitution to greatly expand the scope of what courts regard as supreme law in Canada.